KEAKTIFAN LANSIA DALAM KEGIATAN POSYANDU LANSIA DENGAN TINGKAT KESEHATAN LANSIA DI DESA LEDUG KECAMATAN KEMBARAN KAB. BANYUMAS - Reni Dwi Setyaningsih; Indri Heri Susanti; Danang Tri Yudhono (Viva Medika, 2012)
The number of elderly poeple from year to year is increasing; this hasconsequences on the improvement of services to the elderly one in the village ofLedug. With active in elderly posyandu expected Ledug elderly in the village havea good health status.To determine the relationship between active elderly in theelderly with health posyandu elderly. The research was conducted in the VillageLedug District Kembaran Banyumas. This type of research is quantitative with cross sectional approach.Sampling technique cluster sampling used questionnaire as a means of collectingdata which was distributed to 71 respondents. Analysis of the data used is byusing chi square. The results of this study is a significant relationship exists between theactivity of the elderly with health elderly where P value 0.00 <0.05. Respondentswith high activity have a good health status. A total of 49,3% elderly haveexpressed good health status. In this study a significant relationship exists between the active elderly inthe elderly with health posyandu elderly. Key words: activity, aging, health.